Modernisasi Pendidikan Islam dan Pendidkan Islam Humanis dalam Pandangan Azyumardi Azra dan Tolhah Hasan - Ach. Syaiful; Hafid (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2023)
The strengthening of educational patterns that deviate from the great goals of Islamic religious education means that the thinking of two figures, Azyumardi Azra and Tholhah, needs to be reviewed. This article examines the modernist thoughts of PAI and Humanist PAI from the views of these two figures using a library research approach. The results of this research show that the modernization of PAI starts from Islamic educational institutions such as madrasas and Islamic boarding schools, how Islamic boarding schools can create human resources (HR) for the younger generation who are superior not only cognitively but also affectively and psychomotorically but in accordance with the characteristics and subculture of the Islamic boarding school, namely mastery of religious knowledge. The modernity of Islamic boarding schools also discusses religious knowledge and technological science. Azra places Islamic boarding schools as Islamic educational institutions that remain sub-cultural, but also the knowledge taught at Islamic boarding schools is integrative with the advances of the times, namely science and technology. In Tholhah's view, the weakness of Islamic education, which tends to be dichotomous regarding the issue of humanism, is that it is weak economically and in terms of solidarity, which means that human morals are weak to have integrity in maintaining the values ​​of humanism, which should be a concern. For Tholhah, the big goal of education is to save nature, develop nature's potential, and harmonize nature's journey. Humanity or humanism for Tholhah is nature itself and everything related to humanism is part of what must be considered in Islamic education, including thoughts about modernism in Islamic education.